2015
DOI: 10.1039/c4cp03877k
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic degradation of methylene blue with a nanocomposite system: synthesis, photocatalysis and degradation pathways

Abstract: Three different composites, including a calcined FeOOH supported ZnAl layered double hydroxide (FeOOH-LDO), a calcined ZnAl layered double hydroxide (ZnAl-LDO) and a calcined ZnFeAl layered double hydroxide (ZnFeAl-LDO), were synthesized via a sol-gel method, and their activity for the visible light photocatalytic degradation of methylene blue (MB) was studied. The composites were characterized by PXRD, SEM, and BET techniques, confirming the formation of highly crystalline structures. The activity performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 164 publications
(55 citation statements)
references
References 34 publications
4
51
0
Order By: Relevance
“…On the other hand, other studies show that the basic dye photodegradation mentioned before begins with the opening of the cycle which is in the middle. The latter is constituted by the heteroatoms [26][27][28] N and S. In the light of this bibliography we conclude that basic dyes degradation leads to the formation of several products which are depending on dyes nature of. In addition, three types of mechanisms have been proposed by researchers for the degradation of basic dyes by advanced oxidation.…”
Section: Introductionmentioning
confidence: 80%
“…On the other hand, other studies show that the basic dye photodegradation mentioned before begins with the opening of the cycle which is in the middle. The latter is constituted by the heteroatoms [26][27][28] N and S. In the light of this bibliography we conclude that basic dyes degradation leads to the formation of several products which are depending on dyes nature of. In addition, three types of mechanisms have been proposed by researchers for the degradation of basic dyes by advanced oxidation.…”
Section: Introductionmentioning
confidence: 80%
“…As shown in Figure 10b, the removal efficiency towards MB decreased from 100% at pH = 2 to 40% at pH = 10. From the results, we conclude that the adsorption was effective at acidic pHs (2)(3)(4)(5)(6), because the adsorption of the dye molecules would be facilitated by hydrogen ions (H + ). [66] However, with an increase of pH, chloride anion in MB is exchanged with NaOH to have a displacement reaction, forming NaCl (aq) and MBS + OH − (aq).…”
Section: Effects Of Phmentioning
confidence: 99%
“…Furthermore, the estimated q e values were in good accordance with the experimental q e values. These results suggested that the [46] MOF/GO 183.4 36 30 min [47] Mesoporous MIL-101 22.5 30 2 h [48] MOF-235 187 300 12 h [49] H 3 PW 12 O 40 @Mn ІІІ porphyrin 10.5 10 24 h [50] MOF-Cu-BTC 15.28 3.19 6 h [51] H 6 P 2 W 18 O 62 @Cu 3 (BTC) 3 18.51 40 - [52] Carbon nanotubes 35.4 35 50 min [53] Activated carbon 135 60 10 min [54] Exfoliated grapheme oxide 17.3 30 80 min [55] Nano-ZIF-8 126 60 30 min [56] Graphene oxide 397 34.8 25 min [23] Zn-DDQ 135 500 70 min [60] MIL-100(Fe) 736 30 90 min [61] ErCu-POM (Er-3) 391 20 -…”
Section: Adsorption Kineticsmentioning
confidence: 99%
See 1 more Smart Citation
“…1,2 The development of e±cient photocatalysts is critical for practical application of the photocatalysis technology. The reported metal-based photocatalyst systems, to the best of our knowledge, can be generally classi¯ed as oxides or oxyhalides, [3][4][5][6][7][8] sul¯des [9][10][11] and oxysalts.…”
Section: Introductionmentioning
confidence: 99%